Text to speech synthesis for numerals into Punjabi language - Singh, Maninder (My University, 2013)
Text To Speech synthesis (TTS) is an online application to convert the text written in a language into speech. The text to speech conversion system enables user to enter text in Punjabi and as output it gets sound. This work presents the steps followed for converting text to speech for Punjabi (Gurumukhi) language and the algorithm used for it. This application helps user to type text and as output it gets the speech. The text inputted may be written by the operator or it may be scanned paper that is converted to speech. Though the user gets its output but still conversion of text to speech is not an easy task. It involves a great deal of work to be performed perfectly. It is difficult to create database of number of phonemes, syllables, words for a particular language. This thesis represents the work done on text to speech synthesis for numerals in which speech waveform is generated and applies it to Punjabi speech synthesis using the general speech synthesis architecture.
Master of Engineering (CSE)
Keywords: TTS; Speech Synthesis; Punjabi Language